Evidence-based classification in paralympic sport: application to football-7-a-side - Raúl Reina (Asociación Española de Ciencias del Deporte, 2014)
Paralympic Committee Classification Code, where the language of the International Classification of Functioning Disability and Health is used. Eligibility for is described in terms of impairment, and the aim of the system is to place athletes into classes according to the extent of activity limitation caused by their physical impairments. CPISRA Football permits the participation of athletes with with hypertonia, ataxia, and atetosis, and the should meet a minimum disability criteria to play football. Minimum disability criteria can be met if an athlete's impairment causes sufficient activity limitation in the activity of interest (passing, running, change of direction, among others). Currently, class profiles provide guidance for classifiers during the appointment of players to appropriate classes. However, classes are differentiated from each other based on qualitative descriptions and there is still opportunity for individual interpretation which decreases consistency among classifiers. This paper review recent and current research in Paralympic athletes with hypertonia, athetosis and ataxia, and link research in two Paralympic sports, IPC athletics and football-7-a-side, for the development of evidence-based classification systems.